Sugar Productivity Assessment of Newly Developed Promising Genotypes of Sugarcane (Journal of Bio-Science, 2011)
Context: The prime concern of cane growers and the sugar industry is to achieve higher sugarcane productivity and high sugar recovery both of which support maximum economic return. This requires newly developed sugarcane genotypes.Objectives: To study the performance of newly developed sugarcane genotypes for plant crop and ratooning ability in U.P. Condition.   Materials and Methods: The performance of newly developed sixteen promising sugarcane genotypes along with three standards check viz.; CoJ64, CoS95255 and CoS767 were evaluated during 2005-07 at Shahjahanpur, Uttar Pradesh, India. Results: The experimental results revealed that significantly higher commercial cane sugar (CCS) yield was observed by the genotype UP49 (13.19 t ha-1), CoS06262 (13.67 t ha-1), CoS05263 (13.70 t ha-1), CoS06247 (12.67 t ha-1), CoS05259 (13.12 t ha-1) over three standards CoS767 (9.41 t ha-1), CoJ64 (9.54 t ha-1) and CoS95255 (12.56 t ha-1). The genotype UP49 (10.50 t ha-1) recorded highest CCS% followed by CoS06247 and CoS05263 having 10.49 t ha-1 and 10.29 t ha-1 respectively in ratoon crop. Amongst all the genotypes UP49, CoS06262, CoS05263, CoS06248, CoS06253, CoS05259 and CoS06263 were proved significantly superior over all the three standards checks in respect of cane yield. Conclusion: The UP49 was found the best performer and superior to widely adopted variety CoS767 in respect of cane yield, commercial cane sugar percent, sugar yield and pol percent in cane; under plant and ratoon crops. Key words: Sugarcane; ratoon; CCS%; sugar yield and productivity.DOI: 10.3329/jbs.v17i0.7099J. bio-sci. 17: 41-44, 2009